A Study on the Domestic Environmental Conditions and Its Impact on the Prevalent Morbidities - Shashwat S Nagar; Hirenkumar B Patel; Niraj Pandit (National Journal of Community Medicine, 2018)
Background: Man is responsible for the pollution of his environ- ment through urbanization, industrialization and other human ac- tivities. The success of any health policy or health care intervention depends upon a correct understanding of socio-economic, envi- ronmental and cultural factors which determine the occurrence of diseases and deaths.